2017
DOI: 10.1182/blood-2016-12-759621
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 expression in DLBCL: reappraisal of immunohistochemistry with new criteria for therapeutic biomarker evaluation

Abstract: Overexpression of the BCL2 is associated with a poor prognosis in diffuse large B-cell lymphoma (DLBCL). The assessment of MYC immunohistochemistry (IHC) is becoming optimized, whereas the criteria for BCL2 positivity are highly variable. Furthermore, data on the frequency and prognostic value of BCL2 positivity are conflicting. We aimed to evaluate BCL2 expression by IHC and assess the prognostic significance of the histopathologically scored BCL2 expression in 456 patients with DLBCL uniformly treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 45 publications
6
61
1
2
Order By: Relevance
“…Our findings reveal a strong independent unfavourable prognostic impact of BCL2 expression in PLHIV with DLBCL (HR: 4·48 95% CI: [1·00; 20·10], P = 0·05). These data are consistent with those of several studies in the HIV‐uninfected individuals with DLBCL in which patients were treated with a combined rituximab and doxorubicin‐based regimen (Hermine et al , ; Wilson et al , , ; Rosenwald et al , ; Hu et al , ; Tsuyama et al , ). In the light of our data, BCL2 expression determined by IHC, may allows the stratification of outcomes (Wilson et al , ; Barrans et al , ; Johnson et al , ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings reveal a strong independent unfavourable prognostic impact of BCL2 expression in PLHIV with DLBCL (HR: 4·48 95% CI: [1·00; 20·10], P = 0·05). These data are consistent with those of several studies in the HIV‐uninfected individuals with DLBCL in which patients were treated with a combined rituximab and doxorubicin‐based regimen (Hermine et al , ; Wilson et al , , ; Rosenwald et al , ; Hu et al , ; Tsuyama et al , ). In the light of our data, BCL2 expression determined by IHC, may allows the stratification of outcomes (Wilson et al , ; Barrans et al , ; Johnson et al , ).…”
Section: Discussionsupporting
confidence: 89%
“…Several tumour pathological markers are associated with overall survival in HIV‐negative DLBCL (Alizadeh et al , ; Hans et al , ; Nyman et al , ; Wilson et al , ; Lenz et al , ). BCL2 protein overexpression is a well‐established pejorative prognostic feature in HIV uninfected individuals with DLBCL, especially when combined with MYC overexpression or rearrangement (Hermine et al , ; Wilson et al , ; Rosenwald et al , ; Johnson et al , ; Horn et al , ; Tsuyama et al , ). However, the prognostic impact of BCL2 expression on outcomes in PLHIV and DLBCL is still a subject of debate (Little et al , ; Chadburn et al , ).…”
mentioning
confidence: 99%
“…A major limitation of the IPI system is that it does not allow the incorporation of newly discovered prognostic factors, most notably BCL2 and MYC. BCL2 and/or MYC expression in DLBCL is associated with aggressive behavior and poor prognosis (9,35,36,53). However, the proportional cut-off points of their expressions are still arbitrary, and a recent study has shown the importance of intensity of BCL2 expression as well as its extent (36).…”
Section: Discussionmentioning
confidence: 99%
“…BCL2 and/or MYC expression in DLBCL is associated with aggressive behavior and poor prognosis (9,35,36,53). However, the proportional cut-off points of their expressions are still arbitrary, and a recent study has shown the importance of intensity of BCL2 expression as well as its extent (36). To overcome this limitation and produce an objective, the continuous variable for measuring protein expression, multiplex IF for BCL2 and MYC with tumor marker CD20 was exploited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation